Additional Protection for Geographical Indications in India: A Working of Section 22 (2) of Indian GI Act (Journal of Intellectual Property Rights (JIPR), 2023)
While Article 22 of the TRIPS Agreement grants a common minimum standard of GI protection to all goods, by virtueof Article 23 of TRIPS, ‘wines and spirits’ are given a higher level or additional protection, which is a complimentaryprotection in addition to the Article 22 common protection. At the national front, India has the highest registrations of GIs inagricultural and handicrafts classes of goods. Section 22 (2) and (3) of Geographical Indications of Goods (Registration &Protection) Act, 1999 enable India to grant additional protection to ‘certain goods’ - the expression ‘certain goods’ is notdefined in the Act. Section 22 (2) grants the Central Government, the authority to provide additional protection to certainclass of goods by publishing a notification in the Official Gazette to that effect. When Article 23 of TRIPS Agreementsqualifies only wines and spirits for higher level protection; the Indian GI statute does not restrict the additional protection toany specific class/es of goods. This paper critically examines the ‘working of section 22 (2) of Indian GI Act.’